2013
DOI: 10.1038/ismej.2013.27
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of endosymbiosis: replacements, co-speciation and promiscuity of bacteriocyte symbionts in weevils

Abstract: The processes and mechanisms underlying the diversification of host-microbe endosymbiotic associations are of evolutionary interest. Here we investigated the bacteriocyte-associated primary symbionts of weevils wherein the ancient symbiont Nardonella has experienced two independent replacement events: once by Curculioniphilus symbiont in the lineage of Curculio and allied weevils of the tribe Curculionini, and once by Sodalis-allied symbiont in the lineage of grain weevils of the genus Sitophilus. The Curculio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 51 publications
2
80
0
Order By: Relevance
“…Parallel cases of symbiont-driven ecological expansion have been documented in other insects, including cockroaches (15,16), ants (17), lice (18), and beetles (19)(20)(21). Examples extend into other animal hosts although, in some, transmission may be partly or wholly horizontal rather than strictly vertical.…”
Section: Evolutionary Opportunities From Symbiosis: Ecological Benefimentioning
confidence: 93%
“…Parallel cases of symbiont-driven ecological expansion have been documented in other insects, including cockroaches (15,16), ants (17), lice (18), and beetles (19)(20)(21). Examples extend into other animal hosts although, in some, transmission may be partly or wholly horizontal rather than strictly vertical.…”
Section: Evolutionary Opportunities From Symbiosis: Ecological Benefimentioning
confidence: 93%
“…While the Nardonella symbionts have been conserved among diverse weevils and cospeciated with the weevil hosts for over 100 My (23)(24)(25)(26)(27)(28)(29)(30)(31), previous studies have identified a number of weevil lineages in which the Nardonella symbiont had been either lost or replaced by novel bacterial symbionts (23,24,(32)(33)(34)(35). The extremely reduced Nardonella genome down to 0.2 Mb (Fig.…”
Section: Insights Into Symbiont Replacements and Diversification In Ementioning
confidence: 98%
“…Despite the longlasting host-symbiont coevolution, Nardonella's biological role has been poorly understood (26). Previous studies have identified a number of weevil lineages in which Nardonella infections have been lost or replaced by different bacterial lineages, uncovering a strikingly dynamic aspect of the endosymbiotic evolution in the insect group (23,24,(32)(33)(34)(35).…”
Section: Significancementioning
confidence: 99%
“…In certain instances, evolutionary change may be facilitated by among-microbe transfer of symbiosis-related gene clusters via "symbiosis islands" (Finan 2002), equivalent to pathogenicity islands in pathogenic bacteria, or by the displacement of one microbial partner by another taxon with different traits (Koga et al 2013;Toju et al 2013). With the dramatically improving genomic technologies, it is becoming increasingly feasible to answer these fundamental questions.…”
Section: Concluding Commentsmentioning
confidence: 99%